Optimization of Shelf Arrangement of High Rack Pharmaceutical Cold Store Based on Field Synergy Theory - Liu Yudong; Guan Jiajia; Qi Di; Zhao Chuangyao; Li Angui (Zhileng xuebao)
The temperature and humidity distribution of the pharmaceutical warehouse will affect the efficacy of medicine. This paper takes an elevated stereoscopic medical cold storage in Tianjin to discuss the influence of different shelf layout on the distribution of temperature and humidity. The internal airflow distribution of the cold storage is optimized, and combined with the field coordination theory, the temperature and humidity distribution, temperature and humidity uniformity and refrigeration effect are systematically discussed. The results show that the field synergy angle can effectively be used to evaluate the performance of high rack cold store. Increasing the spacing between shelf layers optimizes the thermal performance of the pharmaceutical cold store. When the shelf layer spacing is 0.6 meters, the average temperature is 4.56°C, the temperature inhomogeneity coefficient (Kt) is 0.039, average relative humidity 55.21%, relative humidity inhomogeneity coefficient 0.015 , and the average field synergy angle (α) is 57.47°, resulting in a more uniform and reasonable temperature field. In this paper, the field synergy Angle is introduced into the optimization research of elevated pharmaceutical cold storage, which provides a theoretical basis for the improvement of pharmaceutical storage design.